The Evolution of Exudativory in Primates 2010
DOI: 10.1007/978-1-4419-6661-2_5
|View full text |Cite
|
Sign up to set email alerts
|

Influences on Gum Feeding in Primates

Abstract: This chapter reviews the factors that may affect patterns of gum feeding by primates. These are then examined for mixed-species troops of saddleback (S. fuscicollis) and mustached (S. mystax) tamarins. An important distinction is made between gums produced by tree trunks and branches as a result of damage and those produced by seed pods as part of a dispersal strategy as these may be expected to differ in their biochemistry. Feeding on fruit and Parkia seed pod exudates was more prevalent in the morning wherea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 47 publications
(45 reference statements)
2
11
0
Order By: Relevance
“…Histochemical tests showed that secretory ducts are rich in polysaccharides, pectins, mucilages and proteins, and in the intercellular spaces of the axial parenchyma of the phloem and secondary xylem in A. peregrina exudates. Similar compounds also are reported for Azadirachta indica (Meliaceae) (Rajput et al, ) and of Ailanthus excels (Simaroubaceae) (Shah & Babu ), gum trees exploited by Microcebus griseorufus (Smith, ). This suggests that these exudates are mainly composed of proteins, polysaccharides, probably pectin.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Histochemical tests showed that secretory ducts are rich in polysaccharides, pectins, mucilages and proteins, and in the intercellular spaces of the axial parenchyma of the phloem and secondary xylem in A. peregrina exudates. Similar compounds also are reported for Azadirachta indica (Meliaceae) (Rajput et al, ) and of Ailanthus excels (Simaroubaceae) (Shah & Babu ), gum trees exploited by Microcebus griseorufus (Smith, ). This suggests that these exudates are mainly composed of proteins, polysaccharides, probably pectin.…”
Section: Discussionsupporting
confidence: 77%
“…The diet of primates may include vegetable exudates, such as gums and saps, which are produced by the secretory ducts of plants (Harrison & Tardif, ; Ushida, Fugita, & Ohashi, ). Marmosets of the genus Callithrix Erxleben, 1,777 (Cebidae) are reported to consume exudates from several species in the plant family Fabaceae (Smith, ), including Anadenanthera colubrina (Vell.) Brenan (= A. macrocarpa (Benth) Brenan.)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vegetables may be included to ensure the diet will not lead to an energy deficit, and as a source of fiber. Gum exudate is more difficult to replace because of its unique chemical composition of soluble fiber, high Ca:P ratio, and cocktail of secondary metabolites [Smith, , ]. Luckily, gum arabic from the Acacia senegalensis can be sourced in raw or refined form in most countries because of its use in the food and cosmetic industries.…”
Section: Discussionmentioning
confidence: 99%
“…Plant exudates are consumed by at least 20% of primate species worldwide, mainly by species of the Calitrichidae family (Smith 2010). Marmosets are the callitrichids that are most likely to feed on gum, having a diet based about 70% on plant exudates due to their high availability (Coimbra-Filho & Mittermeier 1977).…”
mentioning
confidence: 99%